The mark of the sacred - Dupuy, Jean-Pierre; DeBevoise, M. B. (Cultural memory in the present, 2013)
Jean-Pierre Dupuy, prophet of what he calls ""enlightened doomsaying, "" has long warned that modern society is on a path to self-destruction. In this book, he pleads for a subversion of this crisis from within, arguing that it is our lopsided view of religion and reason that has set us on this course. In denial of our sacred origins and hubristically convinced of the powers of human reason, we cease to know our own limits: our disenchanted world leaves us defenseless against a headlong rush into the abyss of global warming, nuclear holocaust, and the other catastrophes that loom on our ho